Analisis Pengaruh Kebugaran Jasmani Terhadap Pencapaian Hasil Kompetisi Persidom Pada Liga 4 Nasional Tahun 2025 - Iman Zulfikar; Achmad Sandi Pratama; Taufiq Hidayat; Riski Ramadhan (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
This study aimed to evaluate the contribution of physical fitness components to the competititve performance of the PERSIDOM Dompu’s football team in the 2025 National League 4. A total of 23 players were assessed for VO₂Max, agility, muscular strength, and flexibility (sit and reach). The team demonstrated consistent performance, earning 21 points from 12 matches. Data were analysed using the Shapiro Wilk normality test, Perason correlatrion, and multiple linear regression. The results indicated that VO₂Max was significantly correlated with competititve performance (r = 0.681; p = 0.001), followed by agility (r = -0.599; p = 0.004) and muscular strength (r = 0.473; p = 0.024). In contrast, flexibility showed no significant relationship (p = 0.181). The regression model revealed that 61.9% of the variance in competitive performance could be explained by the physical fitness variables (R² = 0.619; p < 0.001), with VO₂Max emerging as the strongest predictor (B = 0.362; p = 0.002). These findings highlight the importance of aerobic capacity, agility, and muscular strength in supporting competitive performance, while flexibility plays a more preventive role in reducing injury risk